Healthcare and elderly care in Europe : institutions, challenges, and solutions for better coordination /: institutions, challenges, and solutions for better coordination. ([2023]) - Bahle, Thomas; Ariaans, Mareike; Koch, Katharina; Wendt, Claus
No abstract available